Angry waters - Morey, Walt.; Cuffari, Richard, 1925-1978 (New York, Dutton, 1969)
Paroled to a dairy farm, a 15-year-old slowly develops an interest in the farm and its animals and through this exposure acquires the strength to resist the influence of old friends.
Keywords: Farm life -- Fiction; Juvenile delinquency -- Fiction